2018
DOI: 10.21831/cp.v38i3.21583
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student’s Affective Competencies (Minimizing Hoax) Through the Implementation of Character-Based Economic Learning and Teacher’s Reinforcement

Abstract: Minimizing hoaxes that occur in students is closely related to learning outcomes in the affective domain. Therefore, the purpose of this research is to find out and analyze implementation of character-based economic learning and teacher’s reinforcement influence on student’s affective competence. Type of this research is descriptive and associative analysis. The populations of this research were class of senior high school student in East Jakarta amounting to 1793 students. The sample in this research amounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…In relation to the strategy of developing entrepreneurial interest through learning, Alimudin [20] conducted a study entitled "Strategies for developing entrepreneurial interests through the learning process" giving some suggestions, that in order to increase entrepreneurial interest for vocational students needed: (1) appropriate learning methods and project-based; (2) appropriate learning evaluation method (portfolio); (3) examples of interesting entrepreneurial profiles; (4) business partners who are committed as a place of business incubator for students participating in entrepreneurship subjects; (5) the atmosphere of the learning room that is in accordance with the topic of learning and equipped with multi-media devices and teaching aids; (6) learning design with structured assignments; and (7) the competence of teaching teachers who are able to create an interesting learning atmosphere for students.Complementing several research findings as described above, Hendro et al [21] conducted a study entitled "Implementation of character learning and reinforcement of economic learning and its effect on students' affective competencies in minimizing hoaxes", found that: (1) simultaneously positive and significant influence on the implementation of character-based economic learning and teacher reinforcement on students' affective competencies to reduce hoax news on online social media; (2) teacher reinforcement has a positive but not significant effect on students' affective competencies; (3) as a whole (the implementation of character-based learning and reinforcement of teachers) has an effect of 43.50% on students' affective competencies, including in readiness for entrepreneurship; and (4) there are still many other factors (amounting to 56.50%) that contribute to affective competencies that have not been revealed in this study, hence further research is needed. Another factor that also needs to be taken into account is how much the demand for life skills in the 21st century (which includes critical thinking, creative and innovation, collaborative, and communicative), has a significant effect on entrepreneurial readiness?…”
Section: Resultsmentioning
confidence: 78%
“…In relation to the strategy of developing entrepreneurial interest through learning, Alimudin [20] conducted a study entitled "Strategies for developing entrepreneurial interests through the learning process" giving some suggestions, that in order to increase entrepreneurial interest for vocational students needed: (1) appropriate learning methods and project-based; (2) appropriate learning evaluation method (portfolio); (3) examples of interesting entrepreneurial profiles; (4) business partners who are committed as a place of business incubator for students participating in entrepreneurship subjects; (5) the atmosphere of the learning room that is in accordance with the topic of learning and equipped with multi-media devices and teaching aids; (6) learning design with structured assignments; and (7) the competence of teaching teachers who are able to create an interesting learning atmosphere for students.Complementing several research findings as described above, Hendro et al [21] conducted a study entitled "Implementation of character learning and reinforcement of economic learning and its effect on students' affective competencies in minimizing hoaxes", found that: (1) simultaneously positive and significant influence on the implementation of character-based economic learning and teacher reinforcement on students' affective competencies to reduce hoax news on online social media; (2) teacher reinforcement has a positive but not significant effect on students' affective competencies; (3) as a whole (the implementation of character-based learning and reinforcement of teachers) has an effect of 43.50% on students' affective competencies, including in readiness for entrepreneurship; and (4) there are still many other factors (amounting to 56.50%) that contribute to affective competencies that have not been revealed in this study, hence further research is needed. Another factor that also needs to be taken into account is how much the demand for life skills in the 21st century (which includes critical thinking, creative and innovation, collaborative, and communicative), has a significant effect on entrepreneurial readiness?…”
Section: Resultsmentioning
confidence: 78%
“…The focus of learning is on not only students' competence, but also the development of their character. Even though in dissimilar contexts, there is a simultaneously positive and significant effect of the implementation of character-based economic learning and teacher reinforcement on students' affective competencies (Prasetyono, Abdillah, Widiarto, & Sriyono, 2018) This means that efforts need to be made to increase teachers' understanding of character, and ways of strengthening students' character. In relation to this, this character-based assessment model would be one of the solutions to these problems.…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, kreatifitas guru dalam mengajar juga menjadi isu penting. Hasil penelitian dari The Trends in International Mathematics and Science Study (TIMSS) tahun 2015 memperlihatkan guru dan siswa dalam melakukan interaksi saat pembelajaran belum merangsang dalam peningkatan kemampuan berfikir analitis dan aras tinggi (Prasetyono et al, 2018).…”
Section: Pendahuluanunclassified